Comparing the mannitol-egg yolk-polymyxin agar plating method to the three tube most probable number method for enumeration of bacillus cereus spores in raw and high-temperature-short-time pasteurized milk - Harper, Nigel Murray (Kansas State University, 2009)
The Food and Drug Administration’s Bacteriological Analytical Manual recommends two enumeration methods for Bacillus spp.: 1) standard plating method using mannitol-egg yolk-polymyxin (MYP) agar and 2) most probable number (MPN) method with tryptic soy broth supplemented with 0.1% polymyxin sulfate. Preliminary research evaluated three inoculum preparation methods using EZ-Spore™ B. cereus pellets. Two methods involved EZ-Spore™ B. cereus pellets that were dissolved in deionized (DI) water, grown in brain heart infusion broth with manganese sulfate, and then heated to produce spores. The third inoculum preparation method of dissolving EZ-Spore™ pellets only in DI water was the most efficient due to 100% spores being present in the inoculum. Preliminary research also determined that MPN method recovered greater (p<0.05) B. cereus populations than MYP method in inoculated ultra-high temperature pasteurized skim and 2% milk. The objective of the main study was to compare the MYP and MPN method for detection and enumeration of B. cereus in raw and high-temperature-short-time pasteurized skim, 2%, and whole milk at 4 °C for 96 h. Milk samples were inoculated with B. cereus EZ-Spores™ dissolved in DI water and sampled at 0, 48, and 96 h after inoculation. No differences (p>0.05) were observed among sampling times so data was pooled for overall mean values for each treatment. The overall B. cereus population mean of pooled sampling times for MPN method (2.59 log CFU/mL) was greater (p<0.05) than MYP plating method (1.89 log CFU/mL). B. cereus populations ranged from 3.40 log CFU/mL to 2.40 log CFU/mL for inoculated milk treatments for MYP and MPN methods, which is well below the necessary level for toxin production. Even though MPN method enumerated more B. cereus, the MYP method should be used by industry for enumeration of B. cereus due to its ease of use and rapid turnover time (2 d compared to 5 d with MPN). However, MPN method should be used for validation research due to its greater populations recovered. EZ-Spore™ B. cereus pellets were found to be an acceptable spore inoculum for validation research because the inoculum consists of 100% spores and does not contain vegetative cells.
Keywords: Bacillus cereus; Milk; Mannitol-egg yolk polymyxin agar; Most probable number; Raw milk; HTST milk; Agriculture, Food Science and Technology (0359)